An analysis of virtual fracture clinics in orthopaedic trauma in the UK during the coronavirus crisis. Issue 7 (July 2020) - Rhind, John-Henry; Ramhamadany, Eamon; Collins, Ruaraidh; Govilkar, Siddharth; Dass, Debashis; Hay, Stuart
Abstract : Virtual fracture clinics (VFC) are advocated by new orthopaedic (British Orthopaedic Association) and National Health Service (NHS) guidelines in the United Kingdom. We discuss benefits and limitations, reviewing the literature, as well as recommendations on introducing a VFC service during the coronavirus pandemic and into the future. A narrative review identifying current literature on virtual fracture clinic outcomes when compared to traditional model fracture clinics in the UK. We identify nine relevant publications related to VFC. The Glasgow model, initiated in 2011, has become the benchmark. Clinical efficiency can be improved, reducing the number of emergency department (ED) referrals seen in VFC by 15–28% and face-to-face consultations by 65%. After review in the VFC, 33–60% of patients may be discharged. Some studies have shown no negative impact on the ED; the time to discharge was not increased. Patient satisfaction ranges from 91–97% using a VFC service, and there may be cost-saving benefits annually of £67, 385 to £212, 705. Non-attendance may be reduced by 75% and there are educational opportunities for trainees. However, evidence is limited; 28% of patients prefer face-to-face consultations and not all have access to internet or email (72%). We propose a pathway integrating the VFC model, whilst having senior orthopaedic decision makers available in the ED, during normal working hours, to cope with the pandemic. Beyond the pandemic, evidence suggests the Glasgow model is viable for day-to-day practice. Cite this article: EFORT Open Rev 2020;5:442-448. DOI: 10.1302/2058-5241.5.200041